THU0305 Pharmacokinetics of Switching from Intravenous To Subcutaneous Belimumab for Patients with Systemic Lupus Erythematosus (SLE). (15th July 2016) - Sheikh, S.Z.; Fox, N.L.; Hammer, A.E.; Struemper, H.; Groark, J.; Roth, D.; Gordon, D.
Abstract : Background: The ability to self-administer subcutaneous (SC) belimumab would enhance treatment options for patients with SLE. Objectives: The pharmacokinetics (PK) across the change in administration from monthly belimumab intravenous (IV; 10 mg/kg) to weekly self-administration of belimumab 200 mg SC was examined in patients with SLE. Methods: Study 200339 (NCT02124798 ) enrolled adults with SLE who had received at least three monthly belimumab 10 mg/kg IV doses plus standard care, or who completed the open-label continuation phase of a randomised, controlled trial of belimumab SC (prefilled syringe). The target period between the last IV dose and first SC dose was 1 to 4 weeks. Open-label belimumab 200 mg SC (1 mL) was self-administered weekly (thigh or abdomen) using an autoinjector under clinic observation at Weeks 1, 2, 4, 8 and at home at Weeks 3, 5, 6, 7. PK samples were collected prior to SC administration at Weeks 1, 2, 4 and 8. Results: 95 patients enrolled: 91 completed the study. All except two patients transitioned from belimumab IV administration. Overall, 94% (89/95) of patients successfully self-administered belimumab at Weeks 1 and 2. A total of 736 injections were attempted over the 8-week treatment period, and 720 (98%) were concluded to be successful. Median serum belimumab trough concentration at Week 8 was 113 μg/mL (Figure ). Following the switch from IV to SC, steady-state trough belimumab levels were attained on average by Week 2 (Figure ). Median % changes from Week 1 to Week 8 were -51%, -23%, 1% and -3% for subjects with investigator-reported IV to SC switching time intervals of ≤1.5 weeks, 1.5–2.5 weeks, 2.5–3.5 weeks and >3.5 weeks, respectively. Conclusions: Patients with SLE successfully self-administered belimumab SC using a novel autoinjector. With a protocol-specified 1–4-week interval between the last IV and the first SC administration, baseline (Week 1) belimumab concentrations were on average similar to their eventual steady-state concentration. Since bioequivalent exposures were previously demonstrated for belimumab SC administration with autoinjector and prefilled syringe 1, the pharmacokinetically stable transition from IV to SC administration demonstrated here, is also assumed to hold for belimumab SC administered with the prefilled syringe. The median Week 8 belimumab concentration of 113 μg/mL confirms that steady-state average concentrations over the dosing interval (CavgSS) for weekly belimumab 200 mg SC are similar to the CavgSS of 110 μg/mL for belimumab 10 mg/kg IV every 4 weeks 2 . The appropriate dosing interval between IV to SC dosing appears to be 1–4 weeks to start SC treatment when exposure is close to SC steady-state levels. References: Struemper, H., et al., Clin Pharm Drug Dev, 2015, doi: 10.1002/cpdd.219. Struemper, H., Roth, D., Gordon, D. Arthritis Rheumatol 2014;66(Suppl 10): S292 Acknowledgement: Study funded by GSK. Louisa Pettinger, PhD, Fishawack Indicia Ltd, UK, provided submission assistance funded by GSK. Disclosure of Interest: S. Sheikh: None declared, N. L. Fox Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, A. Hammer Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, H. Struemper Shareholder of: GlaxoSmithKline, Employee of: PAREXEL, J. Groark Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, D. Roth Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, D. Gordon Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline